Semiotic Signs in Avengers Endgame Movie - Rahayu, Tia Rachel; Awaludin, Lili; Sudarisman, Yoga (CALL, 2022)
This study examined the hostile cues in the Avengers: Endgame film. The semiotic theory of Charles Sanders Peirce is used in the debate. It focused on two problem formulations: the type of semiotic sign by highlighting the hostile sign present in the film, and the sign's meaning. Aims of this study was to identify the various hostile semiotic cues present in the film as well as how a film communicates a message that can be applied to daily life. Then, it has significant ideals that can inspire and make reference to societal reality. The study examines a variety of materials, including interview transcripts, social science texts, and narrative-style films, television shows, and periodicals. It does this using a qualitative research methodology called content analysis. In order to be interpreted afterwards, hostile cues from the actors are gathered and grouped. The findings demonstrate that when the Avengers are prepared to make sacrifices in order to battle and defend the universe in order to defeat evil, indicators of animosity are visible.Â Keywords: semiotics, sign, meaning, hostility, movie